(untitled) (Semiárida, 2020)
Shrub thickets are a problem for livestock operations in the semiarid Chaco region because of their low current stocking rate and high hindrance for grazing and personnel movement. We assessed the effect of the following disturbances: roller chopping, aerator, ‘rome’ type disc plow; prescribed fire and pasture resting on standing herbaceous biomass (BIO, kg DM ha-1), shrub density (DEN, plants.ha-1) and individual plant volume (VOL, m3.plant) in southwestern Santiago del Estero from 2008 to 2011 using a block design. Treatment effect had no significant effect on BIO, although resting per se increased BIO 200% and the treatments 20-30% above that threshold. Treatments did not influence DEN but VOL significantly (p > F = 0,0001): the aerator plow showed the smaller plant VOL, but its mean DEN was the highest among treatments. In the short term, the aerator plow increased accessibility for grazing, but in the long term its effect could be negative.